In the absence of streptomycin, minoxidil potentiates the mitogenic effects of fetal calf serum, insulin-like growth factor 1, and platelet-derived growth factor on NIH 3T3 fibroblasts in a K+ channel-dependent fashion - Sanders, D A; Fiddes, I; Thompson, D M; Philpott, M P; Westgate, G E; Kealey, T (Journal of investigative dermatology, 1996)
There is considerable evidence to suggest that the opening of K+ channels plays an important role in stimulating mitogenesis. K+ channel blockers have been shown to inhibit mitogenesis in vitro, mitogens increase cytosolic membrane K+ channel permeability, K+ channel openers stimulate hair growth in vivo, and the Ras/Raf signal transduction pathway induces K+ channel activity. Paradoxically, however, K+ channel openers such as minoxidil have been reported in vitro not to modulate, or even to inhibit, mitogenesis in a range of cell types. Only untherapeutic concentrations have stimulated mitogenesis. These experiments, however, appear to have been carried out in the presence of aminoglycoside antibiotics, which inhibit potassium channel activity. We now report that in the absence of aminoglycoside antibiotics, minoxidil at 10 microg/ml (0.05 mM) causes a significant stimulation of proliferation of NIH 3T3 fibroblasts maintained over a 10-d period in 5% fetal calf serum-supplemented medium. Further, we show that in the presence of 100 microg streptomycin per ml, minoxidil at 10 microg/ml produces an initial inhibition of proliferation, which apparently confirms, in NIH 3T3 fibroblasts, that the inhibition of mitogenesis by minoxidil in the presence of streptomycin is an artifact. The potentiation of NIH 3T3 cell growth by minoxidil can be attributed to the opening of potassium channels, because the potassium channel blocker tolbutamide (5 mM) or combinations of the blockers tolbutamide (1 mM)/tetraethylammonium (2 mM) or glibenclamide (1 microM)/apamin (10 nM) block the minoxidil-induced stimulation of growth. We also demonstrate that minoxidil is able to significantly potentiate the mitogenic effects of both platelet-derived growth factor and insulin-like growth factor 1 on NIH 3T3 fibroblasts in the presence of CPSR-2 (a cytokine free serum substitute). Thus we have shown that minoxidil potentiates the mitogenic effects of fetal calf serum in vitro on NIH 3T3 fibroblasts by opening potassium channels and is also able to potentiate the mitogenic effects of the growth factors platelet-derived growth factor and insulin-like growth factor 1.